1986
DOI: 10.1021/om00133a025
|View full text |Cite
|
Sign up to set email alerts
|

A platinum cluster complex containing a triply bridging carbonyl. The synthesis and structure of (.mu.3-carbonyl)tris[.mu.-bis(diphenylphosphino)methane]-triangulo-triplatinum(2+) hexafluorophosphate

Abstract: Reaction of [PflC^CCF^dppm)], dppm = Ph2PCH2PPh2, with CO in aqueous methanol gives the cluster complex [Pt3(/u3-CO) (ju-dppm)3] [CF3C02] 2 (1) which may be converted to the [PFe]" salt 2. The complexes 1 and 2 are the first complexes reported to contain the Pt3U3-CO) group and are significant as models for CO chemisorbed at a threefold site on a Pt surface. Complexes 1 and 2 were characterized by elemental analysis, IR, and , 31P, and 196Pt NMR and by X-ray crystallography (for 2, as the acetone solvate). Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 0 publications
2
39
0
Order By: Relevance
“…Materials [Pd,(d~pm)~COl(Y = CF3C02,PF6), (7) and [Pt3(dppm),COl-(PF6)2 (8) were prepared according to literature procedures. Methanol (BDH), dichloromethane (BDH), chloroform (BDH), carbon tetrachloride (Anachemia), sodium chloride (Fisher), benzyl chloride (Aldrich Chem.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials [Pd,(d~pm)~COl(Y = CF3C02,PF6), (7) and [Pt3(dppm),COl-(PF6)2 (8) were prepared according to literature procedures. Methanol (BDH), dichloromethane (BDH), chloroform (BDH), carbon tetrachloride (Anachemia), sodium chloride (Fisher), benzyl chloride (Aldrich Chem.…”
Section: Methodsmentioning
confidence: 99%
“…cluster as demonstrated by Puddephatt and co-workers (7,8). The following experiments are performed: (i) measurements of in the presence of CO(g), and (ii) measurements of for the P F 6 and CF3C02-salts.…”
Section: Quantum Yieldsmentioning
confidence: 99%
“…Analysis of the X-ray data showed that the central triplatinum motif in 1 is an almost equilateral triangle with PtePt distances of 2.7361(5), 2.7461(7) and 2.7135(7) Å ( Table 2). The PtePt distances are significantly longer than those reported for other triangular triplatinum complexes synthesized by Puddephatt and coworkers [14,15]. In general, the structure of 1 is analogous to the structure of The internal PtePt distances in 2 are only marginally longer than those observed in 1, however the Pt-halide distances (1, X ¼ Cl; 2 X ¼ Br) were longer in 2 as expected for the heavier halogen atoms, and similar to those observed in the palladium analog.…”
Section: Resultsmentioning
confidence: 53%
“…The kinetics were resolved by means of stoppedflow experiments and are consistent with the proposed mechanism. In the presence of an excess of Bu 4 NOH, an electrocatalytic process was observed with modest turnover numbers (7)(8).…”
Section: A C H T U N G T R E N N U N G (M 3 -Co)a C H T U N G T R E Nmentioning
confidence: 99%
“…Since the first report on the synthesis and characterisation of the [Pd 3 n + throughout this manuscript in which n = 0, 1, 2; dppm = bis-A C H T U N G T R E N N U N G (diphenylphosphino)methane) in the 1980s, by Puddephatt et al, [1][2][3] and its Pt analogue, [4] numerous and exhaustive studies on its reactivity and properties have appeared in the literature. [5][6][7][8][9][10] This cluster exhibits a triangular Pd 3 (M 3 ) centre with three dppm-supported M À M single bonds.…”
Section: Introductionmentioning
confidence: 99%